Peningkatan Kapasitas Kewirausahaan Petani Muda Melalui Pelatihan Aplikasi Canva Sebagai Media Pendukung Pemasaran Digital di Desa Bintang Mas Kabupaten Kubu Raya - Wanti Fitrianti; Jajat Sudarajat; Adi Suyatno (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
ABSTRACT Currently, it shows that the entrepreneurial mindset and involvement in the marketing process among young farmers are still weak. This has implications for the sustainability and income of farming, thereby slowing down farmer regeneration. However, there is potential for farming business development by utilizing digital marketing for the agricultural business interests of young farmer groups in Bintang Mas Village, Kubu Raya Regency. This community service activity (PKM) focuses on increasing the entrepreneurial capacity of young farmers in the context of expanding digital-based marketing activities by providing training in making posters, e-flyers, story feeds, and posts using the Canva application via social media as a promotional tool so that it is hoped that reach a broader market through the use of digital marketing strategies. The results of the training and mentoring showed a positive response and high enthusiasm from participants and an increase in the entrepreneurial capacity of young farmers through digital marketing in the agricultural business. Another result is that the group of young farmers who are partners have been able and skilled in creating promotions designs, logos, and branding which are characteristic of agricultural products uploaded via social media accounts.